Phytochemical Study and Antioxidative Property of Ethanolic Extract from Termitomyces clypeatus - Payel Mitra & , Narayan Chandra Mandal, Anirban Roy, Krishnendu Acharya (Journal of Applied Pharmaceutical Science, 2016)
The present study documents the phytochemical screening and antioxidant properties of ethanolic extract of Termitomyces clypeatus. Phytochemical constituents like phenols, flavonoids and ascorbic acid were much higher than β carotene and lycopene. The analysis of the phenolic compounds performed by HPLC, revealed the presence of pyrogallol (0.223 µg/mg) and cinnamic acid (0.095 µg/mg). Antioxidant activity was evaluated through superoxide radical scavenging assay, DPPH radical scavenging assay, chelating ability, reducing power and total antioxidant capacity determining assays. Their EC50 values ranged from 0.21 µg/ml to 3.22 mg/ml. Result implies that T. clypeatus can not only serve as a food supplement but also be used as treatment for various oxidative stress related diseases.
Keywords: Antioxidant, free radicals, HPLC, phytochemicals.